“Digital Media Shaping Democracy: The need for Media Literacy” - 6. Runcheva Tasev, Hristina. Apostolovska-Stepanoska Milena. (University of Tetovo, 2019)
The paper analyzes the new role of the media in the digital era: whether the end of the information monopoly of traditional news agencies led to diversity of opinions, more freedom and democracy or it created informative chaos and fake news. The process of replacement of daily newspapers with social media as main source of news has resulted with victory of speed over truth, less investigative journalism, news reached through links provided by social networks based on algorithms that decide what news can get through them etc. The multiple sources of informing created increased political awareness and objectivism, but also they contributed towards losing focus on what is important and a lot of fake news. The paper focuses on the free speech and fake news battle. It gives a special focus on the urgent need for media literacy in the era where the internet-caused information apocalypse increases the importance of detecting fake from real. New model of ‘citizen-journalists’ can often mislead the public opinion and can become a threat for truth as much as the fake news. In times when the traditional business model for delivering news is in crisis and the media content is focused on dramatization, simplification, sensationalism, personalization, the media literacy has to become an inevitable part of every democratic society and its educational system.
Keywords: digital media, internet, fake news, citizen-journalist, media literacy.